Membrane engineering: Latest advancements in gas separation and pre-treatment processes, petrochemical industry and refinery, and future perspectives in emerging applications - Iulianelli, Adolfo; Drioli, Enrico (Fuel processing technology, 2020)
The current transformation of our linear and fossil fuels-based economy into a circular economy through the redefined paradigms of the sustainable development is requesting a major role of the renewable sources exploitation and the adoption of alternative technologies able to redesign a new industrial infrastructure not based on the fossil fuel utilization, but involving the concepts of wastes recycle and transformation into added value products. Membrane engineering moves under the principles of the Process Intensification Strategy applied to several industrial sectors, from the chemical and petrochemical industry to refinery, from water desalination and wastewater treatments to agro-food and gas separation etc. This review aims to analyze the impact of the membrane gas separation technology in petrochemical industry and refinery, highlighting the progress done on the membrane materials utilized in various industrial gas separation processes and discussing on the status of the implementation of membrane based operations in the various gas separation industrial fields and related markets. The benefits of their application in terms of improved process efficiency, reduced footprint, environmental protection and lower costs are also proposed. Furthermore, the importance of membrane reactors for fuel processing and membrane based pre-treatments and the integrated membrane gas separation systems is also discussed. •Membrane engineering moves under the principles of the Process Intensification Strategy.•Membrane technology highly impacts in gas separation, petrochemical industry and refinery.•Membrane gas separation represents an alternative technology for a sustainable development.